2017
DOI: 10.1016/j.nbd.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of immunotherapy with antibodies targeting α-synuclein oligomers and fibrils in a transgenic model of synucleinopathy

Abstract: Disorders with progressive accumulation of α-synuclein (α-syn) are a common cause of dementia and parkinsonism in the aging population. Accumulation and propagation of α-syn play a role in the pathogenesis of these disorders. Previous studies have shown that immunization with antibodies that recognize C-terminus of α-syn reduces the intra-neuronal accumulation of α-syn and related deficits in transgenic models of synucleinopathy. These studies employed antibodies that recognize epitopes within monomeric and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 64 publications
(109 reference statements)
3
66
0
Order By: Relevance
“…Furthermore, we have demonstrated that immunization with conformation‐specific monoclonal antibodies reduces α‐syn accumulation and related deficits in wild‐type α‐syn transgenic (line 61) mice (El‐Agnaf et al . ). Moreover, the antibodies were most effective at reducing accumulation of α‐syn oligomers in multiple brain regions and at preventing neurodegeneration (El‐Agnaf et al .…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, we have demonstrated that immunization with conformation‐specific monoclonal antibodies reduces α‐syn accumulation and related deficits in wild‐type α‐syn transgenic (line 61) mice (El‐Agnaf et al . ). Moreover, the antibodies were most effective at reducing accumulation of α‐syn oligomers in multiple brain regions and at preventing neurodegeneration (El‐Agnaf et al .…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 97%
“…Moreover, the antibodies were most effective at reducing accumulation of α‐syn oligomers in multiple brain regions and at preventing neurodegeneration (El‐Agnaf et al . ). Therefore, immunotherapeutic targeting of α‐syn oligomers holds considerable promise in the continued search for disease‐modifying therapies for α‐synucleinopathies.…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 97%
“…Recent work comparing the effectiveness of targeting either oligomers or fibrils validates these in vitro observations as the greatest alleviation of pathology in vivo was achieved via immunotherapy targeted against early‐stage oligomers (El‐Agnaf et al . ). Similarly, the α‐Syn fibrillation inhibitor epigallocatechin gallate has been shown to reduce the membrane interaction and permeabilization of oligomers from the extracellular environment (Lorenzen et al .…”
Section: Cell Models Based On the Treatment With Exogenous α‐Syn Speciesmentioning
confidence: 97%
“…As with intracellular aimed trials of immunotherapy, antibodies targeted toward oligomeric a-Syn have also proven successful at blocking the toxicity of extracellular a-Syn in SH-SY5Y cells in vitro (Emadi et al 2009) and at facilitating the clearance of extracellular aggregates via microglial scavenging (Bae et al 2012). Recent work comparing the effectiveness of targeting either oligomers or fibrils validates these in vitro observations as the greatest alleviation of pathology in vivo was achieved via immunotherapy targeted against early-stage oligomers (El-Agnaf et al 2017). Similarly, the a-Syn fibrillation inhibitor epigallocatechin gallate has been shown to reduce the membrane interaction and permeabilization of oligomers from the extracellular environment (Lorenzen et al 2014).…”
Section: Extracellular Mediated Clearance and Mitigation Of Surface Mmentioning
confidence: 98%
“…68 In a following multicenter, randomized, double-blind, placebo-controlled trial, assessing multiple ascending doses of PRX002 in mild-to-moderate idiopathic PD patients aged 40 to 80 years (Hoehn and Yahr Stages 1-3), both single and multiple doses of this antibody resulted safe, were well tolerated, and produced robust binding of peripheral α-syn as well as dose-dependent increases of PRX002 in cerebrospinal fluid. 67 Several other studies addressed the development of antibodies targeting α-syn, 70,71 including strategies targeting oligomeric forms, [72][73][74] the C-terminus of the protein, 75 or exploiting passive immunization. [76][77][78] Interestingly, some of these approaches were also found to efficiently reduce α-syn propagation.…”
Section: The Possible Approaches To Directly Target α-Syn Pathologymentioning
confidence: 99%